SOCIOECONOMIC DETERMINANTS OF PALM OIL PRODUCTION IN IGBO ETITI LOCAL GOVERNMENT AREA IN ENUGU STATE, NIGERIA - Egwu, Patricia; Odoh, Ngozi; Eze, Anayochukwu (CV. Radja Publika, 2023)
Extant studies have established that Nigeria has lost its place as the global largest producer of palm oil. However, there seems to be a dearth of studies on how the socioeconomic variables of producers affect palm oil production. Consequently, this study analysed the socioeconomic determinants of palm oil production in Igbo Etiti Local Government Area (LGA) in Enugu State, Nigeria. Combinations of multi-stage random and purposive sampling procedures were used to select 120 small-scale palm oil producers. The data collected using a structured questionnaire was analysed with the aid of descriptive statistics of mean, frequency and percentage, and inferential statistical tools of OLS regression and principal component factor analysis. The results reveal that more women (74.2%) dominated palm oil production in the area. The age bracket of most (41.7 %) palm oil producers was between 46-65 years. The overwhelming proportion (70.8%) of the respondents were married with 50.8 percent of them having a household size of between 1-4 persons. The educational level attained by most of the respondents (70.8%) was primary education. 62.5 percent of the respondents had been involved in palm oil production for over 10 years. While the overwhelming proportion (80.8%) of the respondents were not members of cooperative societies. The study found age, education attainment, household size, farming experience, income, and extension contact as the socioeconomic determinants of palm oil production. The study identified financial and institutional factors as the principal factors and constraints to palm oil production in Igbo Etiti LGA of Enugu State. The study concludes that these variables are critical to improving the output of palm oil production in the area. Thus, this should form part of the critical issues to be included in any policy development that targets improvement in palm oil production.